Fund characteristics and their impacts on the performance of hedge funds: an emperical evidence for European and north american hedge fund industries - Hội thảo quốc tế Ngân hàng và Tài chính thế giới 2015 (Trường Đại học Kinh tế, 2020)
In this paper, we investigate the impacts of fund characteristics on the performance of North American hedge funds (NAHFs) and European hedge funds (EHFs) over a period of 1st January 2001 - 31st December 2013. The study period is divided into two sub-sample periods:(1) non-crisis sub-sample period (1st January 2001- 31st December 2007) and (2) during-crisis and post-crisis sub-sample period (1st January 2008 - 31st December 2013), to measure the impact of the global crisis on the results of our study. Our samples consist of 325 North American hedge funds (NAHFs) and 166 European hedge funds (EHFs), which all survive through the sample period. Using the cross sectional regression method, the omega ratios of hedge funds in each sample are regressed against their fund characteristics for a full sample period and sub-sample periods. Results show evidence of the significant impacts of fund strategies on the performance of both NAHFs and EHFs. More fund characteristics are found to have significant impacts on the performance of NAHFs and EHFs during the non-crisis sub-sample period. As compared to NAHFs, the performance of EHFs is rarely affected by theirs fund characteristics during the crisis- and post-crisis sub-sample period.